UPF Autoscaling in Private 5G Networks for Video Transmission: A Comparative Analysis of Reactive and Predictive Approaches - Silva, Pedro Antônio de Andrade da; Maciel Jr, Paulo Ditarso (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF); 2026: Anais do XVII Workshop de Pesquisa Experimental da Internet do FuturoDO - 10.5753/wpeif.2026.24018, 2026)
Industry 4.0 applications demand high reliability and low latency, driving the adoption of Service-Based Architectures in Private 5G networks. However, resource orchestration remains challenging; traditional reactive mechanisms, such as the Kubernetes Horizontal Pod Autoscaler (HPA), fail to address the session affinity of the GPRS Tunneling Protocol. This leads to unbalanced loads where active units saturate while new instances sit idle. This paper proposes a predictive scaling mechanism for the User Plane Function (UPF) that anticipates traffic and instantiates resources prior to session establishment. Validated in a virtualized testbed, the predictive approach ensures proper load balancing and prevents connection drops typical of reactive scenarios.